2014
DOI: 10.1002/sim.6178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the model‐building strategy on inference about nonlinear and time‐dependent covariate effects in survival analysis

Abstract: Cox's proportional hazards (PH) model assumes constant-over-time covariate effects. Furthermore, most applications assume linear effects of continuous covariates on the logarithm of the hazard. Yet, many prognostic factors have time-dependent (TD) and/or nonlinear (NL) effects, that is, violate these conventional assumptions. Detection of such complex effects could affect prognosis and clinical decisions. However, assessing the effects of each of the multiple, often correlated, covariates in flexible multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 71 publications
(185 reference statements)
2
74
1
Order By: Relevance
“…We rely on the backward elimination to select the NL and TD effects into the final flexible multivariable model. Whereas this may raise concerns about potential inflation of type I error and over‐fit bias , both our sensitivity analyses (Table A4) and previous simulations indicated only a negligible impact on our estimates and tests. However, future research should implement and compare alternative strategies for selection of flexible covariate effects .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…We rely on the backward elimination to select the NL and TD effects into the final flexible multivariable model. Whereas this may raise concerns about potential inflation of type I error and over‐fit bias , both our sensitivity analyses (Table A4) and previous simulations indicated only a negligible impact on our estimates and tests. However, future research should implement and compare alternative strategies for selection of flexible covariate effects .…”
Section: Discussioncontrasting
confidence: 55%
“…NL model diverged from our model even more substantially as it (i) failed to detect a significant NL effect of delay and, thus, to select this important prognosticator into the final model and (ii) identified a ‘significant’ NL effect of the SOFA score, which was non‐significant ( p = 0.986) in our model , once adjusted for its significant TD effect (third and fifth columns of Table ). The latter finding reflects the residual confounding between NL and TD effects of the same continuous predictor . As a result, the NL‐only model fits the data much worse than our model ( p = 1.8 * 10 −7 ).…”
Section: Resultsmentioning
confidence: 59%
“…This method does not involve estimating both effects simultaneously and, thus, avoids the issue of nonidentifiability. However, both real‐life analyses and simulation studies showed that the power for testing the NL effects may be substantially reduced if the tests are based on the misspecified model that fails to account for the TD effects of the relevant continuous covariates (Abrahamowicz and MacKenzie, ; Binquet et al., ; Gagnon et al., ; Wynant and Abrahamowicz, ). Indeed, some simulation results in Section of the current manuscript indicate that the covariate effects may be biased if the selection of the NL effects is conditional on an incorrect a priori PH assumption.…”
Section: Discussionmentioning
confidence: 99%
“…See also chapter 11 in Royston and Sauerbrei . Abrahamowicz et al and Wynant and Abrahamowicz also described methods for joint estimation of time‐varying and nonlinear effects based on splines. Areas for further work include the extension of the methods proposed in this paper to a setting in which TVEs are modelled using fractional polynomials and to allow selection of functional forms for continuous variables and covariate interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have proposed algorithms for model selection involving both TVEs and transformation of covariates, though all assume fully observed data. We propose an algorithm (the MI‐MTVE algorithm), which provides a model selection procedure for identifying TVEs using multiply imputed data.…”
Section: Testing the Proportional Hazards Assumption And Model Selectionmentioning
confidence: 99%